Doradztwo filozoficzne - dialog jako proces budowania samoświadomości = Philosophical counseling - dialogue as a process of building self-awareness - Piróg, Mirosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article discusses the issue of philosophical counselling, putting it in the perspective of what is most important in it - the counselling conversation. It is presented according to the philosophical tradition as a healing dialogue. Issues related to the formation of a philosophical attitude, worldview change or freedom from belief are also discussed.
Keywords: doradztwo filozoficzne; dialog; rozmowa doradcza; postawa filozoficzna; philosophical counseling; dialogue; counseling conversation; philosophical attitude